Chronobiologically interpreted ambulatory blood pressure monitoring: past, present, and future. Issue 1 (2nd January 2019) - Cornelissen, Germaine; Watanabe, Yoshihiko; Siegelova, Jarmila; Beaty, Larry A; Singh, Raj K; Singh, Ranjana; Singh, Ram B; Delcourt, Alain; Gumarova, Lyazzat; Gubin, Denis; Chen, Chen-Huan; Otsuka, Kuniaki; et al.
ABSTRACT: Research at the Halberg Chronobiology Center focused to a large extent on the monitoring of blood pressure (BP) and heart rate (HR). Self-measurements and later ambulatory BP monitoring yielded new knowledge of interest to basic science and clinical practice. After a brief review of BP measurement, we outline developments in methods of data analysis that paralleled technological advances in the measurement of BP. We review work done in cooperation with colleagues worldwide to illustrate how a chronobiological approach led to the mapping of spontaneous circadian and other rhythms for the derivation of refined reference values and to the assessment of response rhythms underlying chronotherapy. BIOCOS members work in different fields, spanning from cardiology and nutrition to obesity, diabetes, exercise physiology and rehabilitation, but all strive for "pre-habilitation". The early recognition of increased risk can prompt the timely institution of prophylactic intervention. As technology continues to improve, studies on groups are complemented by longitudinal self-surveillance for health maintenance. Longitudinal records serve for the investigation of environmental influences on human physiology, the topic of chronomics. As current advances in technology and wireless communication will likely impact the future of healthcare, chronobiological methods and concepts should be an integral part of this seachange.